2018
DOI: 10.1111/liv.13948
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosis‐matched outcomes between chronic hepatitis B patients with drug‐induced virological response and inactive carriers

Abstract: Background & Aims We compared the risk of hepatocellular carcinoma (HCC) development between patients with chronic hepatitis B (CHB) who achieved virological response (VR; HBV‐DNA < 2000 IU/mL) with nucleos(t)ide analogues (NUCs) treatment (NUC‐VR group) and patients with inactive CHB phase (ICHBP group). Methods To adjust for imbalances between NUC‐VR and ICHBP groups, propensity score matching (PSM) models with 1:1 ratios were performed. Results This study included 2032 patients (n = 1291 in NUC‐VR group and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…However, because HBV is rarely completely eradicated, most patients require life-long AVT. 7,8 Accordingly, current international guidelines recommend entecavir (ETV), tenofovir disoproxil fumarate (TDF) or tenofovir alafenamide (TAF) as first-line antiviral agents for patients with CHB. [9][10][11][12] Of these, renal and bone safety issues have been a major concern with the use of TDF, which has been documented to be associated with proximal renal tubular dysfunction, resulting in significant hypophosphatemia, renal insufficiency and osteomalacia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because HBV is rarely completely eradicated, most patients require life-long AVT. 7,8 Accordingly, current international guidelines recommend entecavir (ETV), tenofovir disoproxil fumarate (TDF) or tenofovir alafenamide (TAF) as first-line antiviral agents for patients with CHB. [9][10][11][12] Of these, renal and bone safety issues have been a major concern with the use of TDF, which has been documented to be associated with proximal renal tubular dysfunction, resulting in significant hypophosphatemia, renal insufficiency and osteomalacia.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recent studies have shown that the use of potent nucleos(t)ide analogues have significantly improved the prognosis of patients with CHB. However, because HBV is rarely completely eradicated, most patients require life‐long AVT 7,8 …”
Section: Introductionmentioning
confidence: 99%
“…However, because HBV is rarely completely eradicated, most patients often require life-long AVTs. [7][8][9] Of the various nucleos(t)ide analogues used as AVT in CHB management, current international treatment guidelines recommend entecavir (ETV), tenofovir disoproxil fumarate (TDF) or tenofovir alafenamide (TAF) as first-line agents. [10][11][12][13] However, the use of these agents is not without risks.…”
Section: Introductionmentioning
confidence: 99%
“…Second, molecular characteristics such as specific mutations at the envelope, core and X proteins as well as novel biomarkers (eg serum HBsAg, hepatitis B core‐related antigen or HBV‐RNA levels) and refined fibrosis markers (eg elastography, fibrotest 30 and enhanced liver fibrosis test 31 ) should be taken into consideration for a greater understanding of pathogenesis. In the era of potent AVT, the most important determinant for HCC development is fibrotic burden 27,32 . Third, although which NUC between ETV vs tenofovir disoproxil fumarate (TDF) is better for preventing liver disease progression among patients with CHB still remains controversial, 33,34 our findings should be validated among patients treated with TDF or tenofovir alafenamide fumarate.…”
Section: Discussionmentioning
confidence: 88%
“…In the era of potent AVT, the most important determinant for HCC development is fibrotic burden. 27,32 Third, although which NUC between ETV vs tenofovir disoproxil fumarate (TDF) is better for preventing liver disease progression among patients with CHB still remains controversial, 33,34 our findings should be validated among patients treated with TDF or tenofovir alafenamide fumarate. Finally, considering that chronic HBV infection is a life-long disease, further evaluation will be needed over a longer AVT administration period (>15 years) to identify trends in HCC incidence longitudinally.…”
Section: F I G U R Ementioning
confidence: 84%